Development of a roll-to-roll hot imprinting process for superhydrophobic polytetrafluoroethylene surfaces. (27th August 2019) - Moon, I Y; Lee, H W; Oh, Y S; Kim, S J; Kim, J H; Kang, S H
Abstract: Potential applications of superhydrophobic surfaces have attracted many researchers. Although numerous methods have been suggested to achieve superhydrophobic surfaces on various types of materials, only a few methods are suitable for process simplicity, productivity and large area applicability. In this study, we developed a roll-to-roll hot imprinting process for superhydrophobic surfaces to overcome such limitations. Hierarchical patterns were fabricated on the roll surface through wire electrical discharge machining. Through the roll-to-roll hot imprinting process using the pattern roll, the hierarchical patterns were transferred to the polytetrafluoroethylene surface. As a result, superhydrophobic surfaces with a water contact angle of 150° or more were obtained.